2023
DOI: 10.3390/molecules28083339
|View full text |Cite
|
Sign up to set email alerts
|

Folic Acid Ionic-Liquids-Based Separation: Extraction and Modelling

Abstract: Folic acid (vitamin B9) is an essential micronutrient for human health. It can be obtained using different biological pathways as a competitive option for chemical synthesis, but the price of its separation is the key obstacle preventing the implementation of biological methods on a broad scale. Published studies have confirmed that ionic liquids can be used to separate organic compounds. In this article, we investigated folic acid separation by analyzing 5 ionic liquids (CYPHOS IL103, CYPHOS IL104, [HMIM][PF6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…The reproductive period is between the ages of 15-49. Many young girls become pregnant before they have reached the height and body mass typical for the age of a young woman, and pregnancy during puberty is a relatively common phenomenon [32][33][34][35]. A deficiency in folic acid at the time of conception is strongly linked to the risk of congenital defects of the brain and spine.…”
Section: Discussionmentioning
confidence: 99%
“…The reproductive period is between the ages of 15-49. Many young girls become pregnant before they have reached the height and body mass typical for the age of a young woman, and pregnancy during puberty is a relatively common phenomenon [32][33][34][35]. A deficiency in folic acid at the time of conception is strongly linked to the risk of congenital defects of the brain and spine.…”
Section: Discussionmentioning
confidence: 99%
“…The main factors investigated in the reactive extraction of muconic acid were pH, temperature, extractant concentration, and time [49][50][51][52]. It was demonstrated that the pH of the aqueous phase has a significant impact on carboxylic acid reactive extraction [15][16][17][18][19]. In reactive extraction, MA can interact with the extractant in one of two ways: (I) by hydrogen-bonding with the undissociated acid molecule, or (II) by the formation of ion pairs when MA is dissociated (pH > pKa), Figure 5.…”
Section: Reactive Extraction Influencing Factorsmentioning
confidence: 99%
“…The reactive extraction approach has recently drawn more attention as a viable and efficient way to remove carboxylic acids from the fermentation broth and is frequently carried out utilizing a combination of extractants and solvents [13][14][15][16][17][18][19]. The classic systems, which include amines or organophosphorus extractants dissolved in organic solvents, have been improved in a substantial number of research articles over the past few decades in terms of sustainability and efficiency [20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, NTDs, which include defects of the spine (spina bifida), brain (anencephaly), as well as encephalocele, are congenital malformations conditions during the structural growth of the neural tube of newborn babies. FA use before and during the first weeks of pregnancy has been shown to reduce the risk of NTDs [7,8,9].…”
Section: Introduction 1folatementioning
confidence: 99%